PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT TERHADAP KINERJA KARYAWAN PT. PLN (PERSERO) RAYON PANAM - Nurzela Nurzela; Samsir Samsir; Rio J.M Marpaung (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This study aims to determine the effects of the Application of Total Quality Management which consists of costumer focus, teamwork, the improvement of the system of continuous, education and training, the involvement and empowerment of employee on employee performance of PT. PLN (Persero) Rayon Panam. The sample used by 80 respondents of the populationt as many 101 employees. Sampling was do by using stratified random sampling. Primary date was collected by questionnaire as an instrument to prove the results of the research, to test the hypothesis in this study is using multiple linear regression analysis with SPSS (Statistical Program For Social Sciences). The results showed that the Total Quality Management which consists of the variable costumer focus, teamwork, the improvement of the system of continuous, education and training, the involvement and empowerment of employee influential positive and significant against the performance of employees PT. PLN (Persero) Rayon Panam is simultaneous and partial. Variable most dominant influential on the performance of employees is teamwork.Keywords : Total Quality Management, performance of employees.